Flux Based Sensorless Speed Sensing and Real and Reactive Power Flow Control with Look-up Table based Maximum Power Point Tracking Technique for Grid Connected Doubly Fed Induction Generator - D.V.N. Ananth; Venkata Nagesh Kumar (IAES Indonesian Section, 2015)
This aim of this paper is to design controller for Doubly Fed Induction Generator (DFIG) converters and MPPT for turbine and a sensor-less rotor speed estimation to maintain equilibrium in rotor speed, generator torque, and stator and rotor voltages. It is also aimed to meet desired reference real and reactive power during the turbulences like sudden change in reactive power or voltage with concurrently changing wind speed. The turbine blade angle changes with variations in wind speed and direction of wind flow and improves the coefficient of power extracted from turbine using MPPT. Rotor side converter (RSC) helps to achieve optimal real and reactive power from generator, which keeps rotor to rotate at optimal speed and to vary current flow from rotor and stator terminals. Rotor speed is estimated using stator and rotor flux estimation algorithm. Parameters like tip speed ratio; coefficient of power, stator and rotor voltage, current, real, reactive power; rotor speed and electromagnetic torque are studied using MATLAB simulation. The performance of DFIG is compared when there is in wind speed change only; alter in reactive power and variation in grid voltage individually along with variation in wind speed.